UJI AKTIVITAS EKSTRAK ETANOL KULIT BATANG TUMBUHAN AFRIKA (Vernonia amygdalina Delile) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PADA MENCIT JANTAN (Mus musculus) HIPERKOLESTEROLEMIA - Miraz’hul Fahmi; Rudi Kartika; Hendra Priatna; Fathur Rahman; Muhammad Haissul Mahrus (PROSIDING SEMINAR KIMIA, 2023)
Blood cholesterol level which were higher than normal is a trigger of various diseases. The objective of the research was to know the anti-hypercholesterol effect of bark African plant. The research about utilization of ethanol extract of bark African plant (Vernonia amygdalina Delile) has been done, it proved could decrease total cholesterol levels in male mice (Mus musculus). In this research sample macerated with ethanol 96% and then concentrated by rotary evaporator, and gained 9,7% of yield. Based on the results of phytochemical test, secondary metabolites compound that contained in bark African plant are alkaloid, flavonoid, triterpenoid, steroid, phenolic and saponin. On antihiperkolesterolemia activity test by using male mice, there are several treatments that negative control (-), positive control (+) and three treatment with different doses i.e. a low doses (7.5 mg/kg BB), middle doses (15 mg/kg BB) and high doses (30 mg/kg BB). The parameter measured was blood serum of male mice by using a Cholesterol Test Strips. From this test it showed that the effectiveness of decreased total cholesterol level at middle doses of 15 mg/kg BB. Keywords: Bark African plant (Vernonia amygdalina Delile), Phytochemicals test, Total cholesterol levels, Cholesterol test strips